A comparison of the heritability estimates obtained from least-squares ANOVA and REML methods - Jain, Anand; Sadana, D K (The Indian Journal of Animal Sciences, 2012)
First lactation records of 683 Murrah buffaloes matined at the NDRI, Karnal, which were progeny of 84 sires, were used for comparing the heritability estimates of some economic traits obtained from REML methods using an animal model with those from the conventional method of feast-squares ANOVA. The heritability estimates obtained from REML method were in general, lower as compared to those from LS-ANOVA method. However, the REML method was more efficient and gave tangible results for the data set used besides having other known desirable properties